Penguatan Kesadaran Mitigasi Banjir Berbasis Kearifan dan Sejarah Lokal melalui Gerakan Hijau di Kelurahan Tabing Banda Gadang, Nanggalo, Kota Padang - Irwan, Irwan; Zusmeli, Zusmelia; Siska, Felia (Universitas Tanjungpura, 2026)
Kelurahan Tabing Banda Gadang is one of the areas vulnerable to flood disasters due to its lowland topography, land-use changes, and the decreasing presence of water-retaining vegetation. In addition to environmental factors, low community awareness of mitigation based on local knowledge also poses a challenge to disaster risk reduction efforts. This community service program aims to strengthen flood mitigation awareness through the integration of local wisdom and local history into a green movement focused on tree-planting activities. The methods employed included educational socialization based on local environmental history, participatory discussions on local wisdom practices in spatial and water management, and collective tree-planting actions in flood-prone areas. A participatory and contextual approach was adopted to foster a sense of community ownership toward the environment while revitalizing local values that support ecological balance. The results indicate an improvement in community understanding of the relationship between environmental change and flood risk, increased awareness of the importance of vegetation as a natural mitigation measure, and the emergence of collective community commitment to maintaining green spaces grounded in local values. This green movement based on local wisdom and history contributes as a sustainable community-based disaster mitigation education model in flood-prone urban areas.